Methods for estimating costs in patients with hyperlipidemia experiencing their first cardiovascular event in the United Kingdom. (2nd September 2017) - Danese, Mark D.; Gleeson, Michelle; Griffiths, Robert I.; Catterick, David; Kutikova, Lucie
Abstract: Aims: Methods for integrating external costs into clinical databases are not well-characterized. The purpose of this research was to describe and implement methods for estimating the cost of hospitalizations, prescriptions, and general practitioner and specialist visits used to manage hyperlipidemia patients experiencing cardiovascular (CV) events in the United Kingdom (UK). Methods: This study was a retrospective cohort study using the Clinical Practice Research Datalink and Hospital Episode Statistics data. Costs were incorporated based on reference costs from the National Health Service, and labor costs from the Personal Social Services Research Unit. The study population included patients seen by general practitioners in the UK from 2006 – 2012. Patients ≥18 years were selected at the time of their first CV-related hospitalization defined as myocardial infarction, ischemic stroke, heart failure, transient ischemic attack, unstable angina, or revascularization. To be included, patients must have received ≥2 lipid-lowering therapies. Outcome measures included healthcare utilization and direct medical costs for hospitalizations, medications, general practitioner visits, and specialist visits during the 6-month acute period, starting with the CV hospitalization, and during the subsequent 30-month long-term period. Results: There were 24, 093 patients with a CV hospitalization included in the cohort. This study identified and costed 69, 240 hospitalizations, 673, 069 GP visits, 32, 942 specialist visits, and 2, 572, 792 prescriptions, representing 855 unique drug and dose combinations. The mean acute period and mean annualized long-term period costs (2014£) were £4, 060 and £1, 433 for hospitalizations, £377 and £518 for GP visits, £59 and £103 for specialist visits, and £98 and £209 for medications. Conclusions: Hospital costs represent the largest portion of acute and long-term costs in this population. Detailed costing using utilization data is feasible and representative of UK clinical practice, but is labor intensive. The availability of a standardized coding system in the UK drug costing data would greatly facilitate drug costing.